A mixed-methods exploration of regular consumers’ experiences of plant-based meat alternatives (PBMA) in Singapore and the United Kingdom - Siti Amelia Juraimi; Aimee E. Pink; Florence Sheen; Jennifer Gatzemeier; Rochelle Embling; Benjamin P.C. Smith (Future Foods)
Research on plant-based meat alternatives (PBMA) often focuses on its initial acceptance among new consumers with limited investigation into consumers who regularly incorporate PBMA in their diets. This study used a mixed methods approach to investigate PBMA consumption patterns, including motivations and barriers to sustained consumption, among 404 regular consumers (defined as PBMA consumption of at least once a week) in Singapore and the UK (SG: n=228; UK: n=176; 57.9 % women; 69.8 % aged 21–40 years old). Quantitative results showed similar PBMA consumption between Singapore and the UK (p=.498) but motives and barriers to sustained consumption and their consumer characteristics (i.e., food choice motives, food neophobia) were significantly different (p<.001). UK consumers showed greater agreement with motivational statements and were more sustainability-driven while Singapore consumers showed greater agreement with barrier statements and valued the impact of food on their body more. Product-related motives (β=0.22, p<.001) and accessibility barriers (β=0.15, p=.024) predicted overall PBMA consumption in both countries. Qualitative results suggest that whilst UK and Singapore consumers were satisfied with PBMA, they wanted higher nutritional quality, greater accessibility to affordable options and a wider variety. Further improvements in these areas could encourage repeated purchases and support the long-term adoption of PBMA.